Экология, распространение и хозяйственное значение галеруки садовой — Galeruca роmоnае Scop. (Coleoptera, Chrysomelidae) на Украине - Бровдий, В.М. (Вестник зоологии, 1972)
Galeruca pomonae Scop, is distributed in all landscape zones of the Ukrainian SSR, but most often it was met in the southern steppe regions of the republic. It winters in an egg phase. In September each of the females lays up to 350 eggs on dry parts of herbaceous plants. Larvae live open in spring on the leaves of Centaurea amara L., Salvia pratensis L., Knautia arvensis С о u l t. and other herbaceous plants. Pupae develop in soil. In beetles a summer diapause is observed lasting for about 40—50 days. A cycle of the species development is monovoltine. The species is registered as an occasional pest of Brassica oleoracea L., B. napus L., Daucus sativus (H о f f m.) Roehl , Beta vulgaris L. and other vegetable crops.